2020
DOI: 10.1021/acs.chemmater.9b04094
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystal Model of Highly Efficient Water-Splitting Photocatalysts: A KTaO3 Wafer Doped with Calcium Cations

Abstract: Alkali tantalates, NaTaO3 and KTaO3, are known as highly efficient semiconductor photocatalysts for the overall water-splitting reaction when properly doped with foreign metal cations. Characterizing surface reaction sites is needed for further development. In this study, (001)-oriented KTaO3 wafers were doped with Ca cations thorough a solid-state reaction to provide platforms for surface science studies. X-ray diffraction showed a Ca-rich perovskite-structured surface layer that covers the Ca-poor or pristin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 67 publications
0
12
1
Order By: Relevance
“…The reported evolution of the hydrogen in the presence of Ag as a dopant in KTaO 3 is 2072 μmol g −1 h −1 . 240–243 The lanthanum and ferrite-based perovskite material are also reported. 244 Table 3 lists various perovskite materials used for water splitting.…”
Section: Perovskite Oxide Based Materialsmentioning
confidence: 99%
“…The reported evolution of the hydrogen in the presence of Ag as a dopant in KTaO 3 is 2072 μmol g −1 h −1 . 240–243 The lanthanum and ferrite-based perovskite material are also reported. 244 Table 3 lists various perovskite materials used for water splitting.…”
Section: Perovskite Oxide Based Materialsmentioning
confidence: 99%
“…Furthermore, the good agreement between experimental data for the Nd and La emitters and the computationally generated model demonstrate that no significant lattice distortions take place around the dopant site. In the light of previous XFH characterizations of the local structure around dopant sites (examples are given in previous studies [ 5–9 ] ), this is a rather unusual situation and may be explained by the stability of the LaF 3 lattice and the same oxidization state of the lanthanides (nominally Nd 3+ and La 3+ ).…”
Section: Resultsmentioning
confidence: 80%
“…Prominent recent examples where XFH was used to investigate the impurity site are the characterization of lattice distortions around Ga impurity atoms in InSb single crystals, [ 4 ] the determination of the spontaneous formation of suboxidic coordination around Co in ferromagnetic rutile, [ 5 ] the determination of different dopant sites in topological insulators like Mn:Bi 2 Te 3 [ 6 ] and In:Bi 2 Se 3 , [ 7 ] the atomic environment around Ca cations in a doped KTaO 3 wafer, [ 8 ] or studying the effect of heavy element doping of Ta in a Fe 2 VAl Heusler‐type thermoelectric material. [ 9 ] XFH is, however, not limited to impurities, but can also be useful for the investigation of bulk samples, in particular for chalcogenide superconductors [ 10 ] and also in general for determining positional fluctuations of atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous XAFS study on BaCa 0.03 Ti 0.97 O 2.97 [28], it was found that the doped Ca ion can occupy the B site despite having the same valence as that of the Ba 2+ ion at the A sites. In addition, the XFH measurements on Ca-doped KaTaO 3 indicated that both A and B sites are substituted by Ca [29]. A similar situation might occur in the case of perovskite oxynitrides CaTaO 2 N. Taking such a structural feature into account, we use the chemical formula (Ca 1−x Ta x )(Ta 1−x Ca x )O 2 N, where x is the fraction ratio of Ca at the B site and that of Ta at A site.…”
Section: Resultsmentioning
confidence: 99%